2020
DOI: 10.3389/fpsyg.2020.581397
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Social Support and Job Satisfaction Among Mainland Chinese Ethnic Minority Kindergarten Teachers: The Mediation of Self-Efficacy and Work Engagement

Abstract: Grounded on the social exchange theory (SET), social cognitive theory (SCT), and self-determination theory (SDT), this study aims to explore the mediating role of self-efficacy (SE) and work engagement (WE) on the effect of social support (SS) on job satisfaction (JS) among Chinese ethnic minority kindergarten teachers (KTs). The results show that: (1) SS has a directly significant effect on JS; (2) WE mediates the relationship between SS and JS; and (3) SE mediates the relationship between SS and WE. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…Employees with high levels of POS presented greater satisfaction with their jobs [86]. According to social exchange theory [20,21], when perceiving strong support from an organization, employees tend to reciprocate by engaging in their jobs and developing loyalty to their organization [25]. In comparison, employees feeling unsupported are likely to feel dissatisfied with their jobs and reduce their commitment to the organization [94].…”
Section: The Mediating Role Of Jsmentioning
confidence: 99%
See 1 more Smart Citation
“…Employees with high levels of POS presented greater satisfaction with their jobs [86]. According to social exchange theory [20,21], when perceiving strong support from an organization, employees tend to reciprocate by engaging in their jobs and developing loyalty to their organization [25]. In comparison, employees feeling unsupported are likely to feel dissatisfied with their jobs and reduce their commitment to the organization [94].…”
Section: The Mediating Role Of Jsmentioning
confidence: 99%
“…Moreover, according to the job demands-resources (JDR) model [24], when perceiving inefficient job resources (e.g., organizational support), employees tend to mobilize individual resources (e.g., SE) and are more likely to be satisfied with their work. Furthermore, some studies have demonstrated that SE controls the association between POS and JS [25,26], with a significantly negative relationship between SE, JS, and JB [3,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The high turnover of kindergarten teachers due to job dissatisfaction is an urgent problem in China especially ( Xia et al, 2022 ). Therefore, kindergarten teachers’ job satisfaction has attracted widespread attention among educators, researchers, and policymakers ( Wu et al, 2020 ). In summary, it is necessary to explore the potential predictors of kindergarten teachers’ job satisfaction to enhance job satisfaction and in turn, reduce turnover rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, less is known about this relationship in kindergarten teachers. To our knowledge, only one study explored this relationship, and found that social support predicted job satisfaction of ethnic minority kindergarten teachers in China ( Wu et al, 2020 ). In the current study, we recruited a sample of general kindergarten teachers to test this relationship, which enriches the research on job satisfaction in kindergarten teachers.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, on the one hand, stock liquidity may promote mergers and acquisitions between enterprises, making managers face the pressure of mergers and acquisitions. Social psychology theory believes that the environmental atmosphere will affect people's motivations, thereby affecting people's behavioral decisions (Kerksieck et al, 2019;Wu et al, 2020). The psychological expectation of mergers and acquisitions (M&A) pressure will aggravate management's short-sighted behavior, thereby reducing corporate innovation (Nguyen and Nguyen, 2020;Garcia-Sanchez, 2021).…”
Section: Introductionmentioning
confidence: 99%